Upaya Pemerintahan Daerah dalam Penggunaan Inovasi Teknologi dalam Perencanaan Pembangunan Pemerintahan Daerah (Studi Kasus di Provinsi Sulawesi Selatan dan Provinsi Sumatera Barat) - Siti Maemunah; Adi Suhendra (Proceedings Series on Physical & Formal Sciences, 2021)
This technological development has become a medium used by a state administrator to improve the welfare or services of its citizens. An innovation to capture this phenomenon is needed. Local government innovation is very important in implementing good and reliable governance (Good Governance). The implementation of regional development always begins with research and development activities, as well as assessments. Development planning is not only done on the table, without seeing the reality on the ground. The core of the planning problem is making the plan itself which includes a series of procedures and involves many parties. The long process and the many parties involved often make planning ineffective. Based on this, this study aimed to compare the differences in planning innovations carried out in two different regions in South Sulawesi and West Sumatra to compare the innovations of the two regions. This study used a qualitative descriptive approach. As a result, South Sulawesi and West Sumatra had different development innovations. South Sulawesi emphasized improving a website-based information system that would be a reference for development planning. Meanwhile, West Sumatra emphasized assessing construction services that would carry out development planning in the West Sumatra region. Suggestions for the future, each agency allocated a budget to increase the capacity of the SIPPD admin management and provide cost consequences as motivation.